VERIFICATION OF ROAD ACCIDENT SIMULATION CREATED WITH THE USE OF PC-CRASH SOFTWARE - Artur ZIOŁA (Scientific Journal of Silesian University of Technology. Series Transport)
The paper discusses an example of PC-Crash software usage for road accident reconstruction. Only a segment of the software capabilities is presented, together with a comparison of the visualized 3D simulation with the actual collision video record.